2018
DOI: 10.1038/s41598-018-27447-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, fungal load, coinfections, histological skin changes, and itraconazole treatment response of cats with sporotrichosis caused by Sporothrix brasiliensis

Abstract: Zoonotic sporotrichosis caused by the fungus Sporothrix brasiliensis is usually severe in cats. This study investigated the associations between clinical features, fungal load, coinfections, histological skin changes, and response to itraconazole in cats with sporotrichosis caused by S. brasiliensis. Fifty-two cats with skin lesions and a definitive diagnosis of sporotrichosis were treated with itraconazole for a maximum period of 36 weeks. The animals were submitted to clinical examination and two subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 36 publications
9
66
0
8
Order By: Relevance
“…Similarly, in humans and dogs, the occurrence of lesions with high fungal burdens is usually associated with immunosuppressive conditions, such as malnutrition, use of steroid, and the presence of underlying diseases, especially those that induce immunosuppression, such as AIDS [ 27 , 28 , 29 , 30 , 31 , 32 ]. In cats, Miranda et al [ 7 , 33 ] and Souza et al [ 13 ] have already observed that different immune response patterns determine the intensity of the fungal burden in skin lesions of feline sporotrichosis and that large numbers of fungal cells generally occur in lesions with a poorly organized inflammation. In addition, a negative correlation has been observed between fungal burden and the number of lymphocytes, neutrophils, and macrophages [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in humans and dogs, the occurrence of lesions with high fungal burdens is usually associated with immunosuppressive conditions, such as malnutrition, use of steroid, and the presence of underlying diseases, especially those that induce immunosuppression, such as AIDS [ 27 , 28 , 29 , 30 , 31 , 32 ]. In cats, Miranda et al [ 7 , 33 ] and Souza et al [ 13 ] have already observed that different immune response patterns determine the intensity of the fungal burden in skin lesions of feline sporotrichosis and that large numbers of fungal cells generally occur in lesions with a poorly organized inflammation. In addition, a negative correlation has been observed between fungal burden and the number of lymphocytes, neutrophils, and macrophages [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cats, Miranda et al [ 7 , 33 ] and Souza et al [ 13 ] have already observed that different immune response patterns determine the intensity of the fungal burden in skin lesions of feline sporotrichosis and that large numbers of fungal cells generally occur in lesions with a poorly organized inflammation. In addition, a negative correlation has been observed between fungal burden and the number of lymphocytes, neutrophils, and macrophages [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preponderance of lesions to aggregate at these cooler sites, especially at the ear tips, may be due to the lack of thermotolerability of S. s. sensu stricto and S. globosa isolates compared with S. brasiliensis which has the propensity to disseminate in a susceptible feline host [24][25][26] (Fig. 5).…”
Section: And 4)mentioning
confidence: 99%